Analisis Fixed Carbon Biochar Dengan Bahan Baku Sekam Padi - Harsena Hayas Fika; Shinta Elystia; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Biochar is a soil amendment agent that has long been known in agriculture which is useful for increasing soil productivity. The raw materials for making biochar come from agricultural, plantation, livestock and forestry residues. Rice husks contain 75-90% organic matter (cellulose and lignin), silica minerals and other micro elements so they are good for use as soil amendments. Biochar is made by pyrolysis at 500 0C for 1 hour and flows 0.1 L / minute of N2 gas. Biochar from rice husks in this study has met the minimum fixed carbon requirements based on SNI 06-3730-1995, namely 68.4%. Key words : Biochar, rice husk, fixed carbon